Immune checkpoint inhibitors in breast cancer treatment - Amer, Fatma (faculty of Basic Medical Science - Libyan International Medical University, 2019)
Breast cancer is a major cause of cancer-related death among women worldwide. Currently breast cancer is one of the major cancer types for which new immune-based cancer treatments are in development. Triplenegative breast cancer (TNBC), is characterized by a lack of expression of estrogen receptor (ER), progesterone receptor (PR), and HER2/ neu. TNBCs are generally high-grade, aggressive tumors with a high rate of distant metastasis and limited treatment options. Novel therapeutic strategies are needed to improve the management of patients with TNBC. A promising avenue of clinical research in breast cancer is the use of immune checkpoints. The aim of the study was to evaluate expression levels of selected immune checkpoints- PD-1 (programmed cell death protein 1), and PD-L1 (programmed cell death 1 ligand 1) in breast cancer patients. Immunogenicity appears to be gaining importance in triple negative and HER2-positive molecular subtypes of breast cancer, and the results in this study provide a basis for further investigation into the role of immune checkpoints in breast cancer.
Unlike other solid tumor types, such as melanoma with elevated mutational load, thus activating an antitumor immune response, breast cancer has not traditionally been thought to be immunogenic. But recent studies on tumorinfiltrating lymphocytes, immune milieu, checkpoints and significant heterogeneity within breast cancer subtypes, have cast new light on the role of immune system in breast cancer. [3] In recent years, immunotherapy has emerged as a possible fourth leader after surgery, chemo and radiotherapy, targeting cancer not by its anatomic location or tendency to divide, but by the inherent mechanisms the immune system uses to distinguish between healthy and pathologic tissue. The immune system is amazingly complex. It can recognize and remember millions of different enemies, and it can produce secretions and cells to match up with and wipe out each one of them. Scientists have discovered that the immune system is capable of destroying tumor cells, and that the body defends itself against cancer in much the same way that it defends itself against infection. Harnessing the immune system to recognize and destroy tumor cells has been the central goal of anti-cancer immunotherapy. There are more than one type of immunotherapy: Monoclonal antibodies (MABs), Checkpoint Inhibitors, Cytokines, Vaccines to treat cancer and CAR T-cell therapy.[2]